Hans Kelsen and Carl Schmitt : a juxtaposition - Diner, Dan 1946- (ham- Māḵôn le-Hisṭôryā Germānît <Tēl-Āvîv>: Schriftenreihe des Instituts für Deutsche Geschichte, Universität Tel Aviv, 1999)
Proceedings of a conference on Kelsen and Schmitt held Jan. 5-6, 1997 in Tel Aviv and organized by the Max Planck Institute of European Legal History, Frankfurt/Main and the Institute for German History at Tel Aviv University.